ANALISIS IMPLEMENTASI PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP LINGKUNGAN DAN KESEJAHTERAAN MASYARAKAT PETANI (STUDI KASUS PADA PT. LSI DI KABUPATEN KUTAI BARAT) - Arista Damayanti; Ida Bagus Made Agung Dwijatenaya; Hyohana Hekiya (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
This study aims to determine the effect of CSR on the environment and on the welfare of the farming community and the influence of the environment on the welfare of the farming community by PT. LSI. This research was conducted in Perigiq Village, Jempang District, Mancong Jempang District, Muara Nayan Jempang District and Gunung Bayan District Muara Pahu Kutai Barat Regency. The research design uses a quantitative research approach, and with data collection techniques through interviews, observations, and documentation. The population in this study was 223 based on the number of farmers, using Simple Random Sampling with a sample of 69 respondents, the analytical test used was SmartPLS v.3.0 with SEM (Structural Equation Modeling) analysis method.The results of the study show that the influence of CSR on the environment has a positive and significant effect, this result is based on the calculation of Path Coefficients obtaining a value of 0,347 > 0 which is declared positive and the T-Statistic calculation obtains a value of 2,952 > 1,96 which states significant. The influence of CSR on Welfare has a positive and significant effect, this result is based on the calculation of Path Coefficients obtaining a value of 0,339 > 0 which is declared positive and the T-Statistic calculation obtains a value of 2,607 > 1,96 which states significant. The influence of the environment on welfare has a positive but not significant effect, the environment has a positive but not significant effect on well-being, this result is based on the calculation of Path Coefficients obtaining a value of 0,229 > 0 which is declared positive and the T-Statistic calculation obtains a value of 1,785 < 1,96 which states that it is not significan, this is because the company has nit yet cared for social responsibility.